Publishing in management: Exhilaration, bafflement and frustration - Wright, Mike (Institutional Knowledge at Singapore Management University, 2020)
Scholars find the journal publishing process exhilarating, baffling and frustrating in equal measure. The professional joy and excitement of receiving an acceptance letter following a long drawn-out process inwhich you have diligently responded to successive rounds of reviewers’ comments is probably only matched by a letter awarding a research grant. Contrast this to the sense of dejection and distress that accompanies a rejection letter. This is further exacerbated if the reviewers’ comments and decision appear to be harsh and if they make little sense. It is even more disappointing if the paper appears to have beenprogressing through different rounds of reviewing only to be rejected late in the process. Therefore, we have to start all over again. We may not realize it but academics are not dissimilar to actors in that they constantly have to audition their work in journals or to research funders. Learning to live with rejection is a key part of the role. We cannot be successful with every submission.